The Role of Resistance and Plyometric Training in Firefighter Safety and Performance: A Narrative Review - Austin A. Kohler; Andrew R. Moore; Angelia M. Holland-Winkler (Physiologia)
Firefighting is a physically demanding occupation that requires optimal fitness and coordination in addition to other physical and cognitive skills. When firefighters lack the physical fitness necessary to perform their duties, they put themselves and others in danger of injury and even death. The heavy, unbreathable personal protective equipment worn to shield firefighters from harmful conditions also promotes overall performance decrements via restricted range of motion as well as energy expenditure and heat-related fatigue. Firefighters are expected to carry other heavy loads, such as hose packs, tools, and victims, while working in hazardous environments. In addition to external load carriage, many firefighters also carry excess body fat that may contribute to poor physical fitness and performance. Therefore, it is imperative to incorporate training strategies to optimize load carriage and improve body composition for improved physical performance during emergencies. Thus, the aims of this narrative review are to (1) explore the impact of firefighter-specific issues on physical performance and safety and (2) identify strategies to assess and optimize occupational performance and safety. Plyometrics; resistance training; and exercise selection, volume, and intensity specifically for improving physical performance in firefighters will be discussed.